2013
DOI: 10.1117/12.2031639
|View full text |Cite
|
Sign up to set email alerts
|

WPSS: watching people security services

Abstract: To improve security, the number of surveillance cameras is rapidly increasing. However, the number of human operators remains limited and only a selection of the video streams are observed. Intelligent software services can help to find people quickly, evaluate their behavior and show the most relevant and deviant patterns. We present a software platform that contributes to the retrieval and observation of humans and to the analysis of their behavior. The platform consists of mono-and stereo-camera tracking, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Experiments with human operators showed that the system leads to a significant reduction of missed people by using the interactive functionality, especially for large time intervals [5]. The tracking system was integrated and validated in a crowded [13] [19] shopping mall in the Netherlands, in collaboration with five SMEs [4]. The system performed consistently and robustly.…”
Section: Graphical User Interfacementioning
confidence: 99%
“…Experiments with human operators showed that the system leads to a significant reduction of missed people by using the interactive functionality, especially for large time intervals [5]. The tracking system was integrated and validated in a crowded [13] [19] shopping mall in the Netherlands, in collaboration with five SMEs [4]. The system performed consistently and robustly.…”
Section: Graphical User Interfacementioning
confidence: 99%
“…These tracks can be used for multi-camera tracking and re-identification [1][19] [6][27] and further behavior analysis [4]. For each person, typically multiple tracks are generated due to presence in different cameras and track fragmentation.…”
Section: Pedestrian Trackingmentioning
confidence: 99%